English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

given f(x)= 5x^2 - 3x+1, find f(-2)
I am thinking that i replace x with -2 right? then go from there. this is so confusing. im 30 yr, i know i should of paid more attention in high school.

2006-11-12 15:06:30 · 10 answers · asked by Anonymous in Science & Mathematics Mathematics

i plugged in -2 and i ended up with -13, and 27. now im really confused.

2006-11-12 15:10:32 · update #1

10 answers

Yes you're correct - just plug in -2 for x to get:

20 - -6 + 1 = 27

2006-11-12 15:08:59 · answer #1 · answered by martina_ie 3 · 0 0

It's ok. I had to do most of the "high school" math twice. Now I am a Math major :)

think of the f(x) as a graph of all possible values of x, hence the "x"

when you want to evaluate a function at a point, you replace the "x" with whatever the constant is (can be letters or numbers)

your problem f(-2) = 5(-2)^2-3(-2)+1; we are evaluating the function at the point x= -2

hope this helps

2006-11-12 15:13:42 · answer #2 · answered by Anthony A 3 · 0 0

15

2006-11-12 15:08:39 · answer #3 · answered by Anonymous · 0 0

Yes, you replace x with -2:

5*(-2)^2 - 3*(-2) + 1

2006-11-12 15:09:27 · answer #4 · answered by arbiter007 6 · 0 0

New examine say the older you grow to be the less sleep you like. although infantrymen in education like BUD'S , determination, PJ's ect are in many situations pushed to accomplish on no extra desirable than 4 hours of sleep each week. It merely relies upon on the state of concepts and motivation of the 21 yo. Ask a pre-med pupil, or a wrecker driving force. the two artwork ungodly hours.

2016-12-14 06:12:52 · answer #5 · answered by ? 4 · 0 0

f(x)=5x^2 - 3x+1
f(-2)=5*(-2)^2-3*(-2)+1
f(-2)=5*4+6+1=27

2006-11-12 15:22:29 · answer #6 · answered by yupchagee 7 · 0 0

You are correct, replace x with -2

Instead of giving you the answer, which you seem to want to work out, I'll tell you instead that f(-3) = 55

2006-11-12 15:12:31 · answer #7 · answered by Gary H 6 · 0 0

5(-2)^2 - 3(-2)+1
5(4) -3(-2)+1
20- -6+1
20+6+1
27

2006-11-12 15:12:03 · answer #8 · answered by R1.8Turbo 1 · 0 0

f(x)= 5x^2 - 3x+1
f(-2) = 5 * (-2)^2 - 3 * (-2) + 1
f(-2) = 5 * 4 - (-6) + 1
f(-2) = 20 + 6 + 1
f(-2) = 27

2006-11-12 15:09:54 · answer #9 · answered by Iwearpants 2 · 0 0

f(-2)=(5*-2^2)-(3*-2)+1
f(-2)=(5*4)-(3*-2)+1
f(-2)=20-(-6)+1
f(-2)=20+6+1= +27

2006-11-12 15:21:08 · answer #10 · answered by Todd D 3 · 0 0

fedest.com, questions and answers